1996
DOI: 10.1002/(sici)1097-010x(19961001)276:2<164::aid-jez10>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic changes in the ampulla of the rat oviduct

Abstract: The mammalian oviduct especially the ampulla part plays an essential role in female reproduction as fertilization, oocyte maturation and early embryonic development. The present study was focused on the microscopic changes of the rat ampulla epithelium during the oestrous cycle and correlates the findings with their possible functions. Twenty five rats of regular 5 day oestrous cycles were used in our study. They were divided into 5 groups; five rats in each phase of estrous cycle (early proestrus, late proest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
3
10
1
Order By: Relevance
“…Both secretory and ciliated cells coexist in the epithelium of the cranial oviductal region, whereas the majority are secretory cells in the caudal oviductal region. The present study dose not support an earlier idea that cilial and secretory epithelial cells are transitory throughout the estrous cycle (39)(40)(41). To explain lineage determination and the cellular distribution pattern, there must be at least two signals released from the neonatal mesenchyme.…”
Section: Discussioncontrasting
confidence: 99%
“…Both secretory and ciliated cells coexist in the epithelium of the cranial oviductal region, whereas the majority are secretory cells in the caudal oviductal region. The present study dose not support an earlier idea that cilial and secretory epithelial cells are transitory throughout the estrous cycle (39)(40)(41). To explain lineage determination and the cellular distribution pattern, there must be at least two signals released from the neonatal mesenchyme.…”
Section: Discussioncontrasting
confidence: 99%
“…Staining intensity in the ampulla increased from proestrous to estrous, suggesting that ovarian steroids regulate leptin and adiponectin expression. These results are consistent with the rapid cyclic changes easily recognized in the gross morphology of the rat oviduct and that are most evident in the ampulla (Shirley and Reeder 1996). In this region, ciliated epithelial cells prevail before ovulation, whereas secretory cells are more numerous at the postovulatory stages.…”
Section: Discussionsupporting
confidence: 89%
“…Non-ciliated secretory cells were predominant among ampullar epithelial cells in estrus after ovulation, and the percentage became highest in metestrus, rapidly decreasing in diestrus. The changes in constitution of ampullar epithelium observed in this study were similar to those reported in rats [6,19]. In hamsters [5], such secretory cells are predominant on the day of ovulation.…”
Section: Discussionsupporting
confidence: 88%